Identification Of Visual Impaired Children & Responses to Recreational Games in Support of Inclusive Tourism - Natasha Indah Rahmani; Dyah Prabandari; Kania Sofiantina Rahayu (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2022)
Encouraging inclusivity in education and urban development is one of the goals in the Sustainable Development Goals (SDGs). The development of inclusive tourism is one way to push the SDGs goals to be achieved. Tourism basically includes several components such as attraction, accommodation and accessibility. In our community, especially children with disabilities, currently still have difficulties in enjoying tourism, this can be caused by all the three components of tourism such as attraction, accommodation and accessibility are not all disability-friendly. The development of disability-friendly recreational games is one way to support the attractiveness component so that it is accessible for people with disabilities. People with dissability have many different condition based on their difficulitites, one of which is people with visual impaired. This study will discuss the response of children with visual impairments to some recreational games that designed specifically for their condition. The method in this research is to use observation and Applied Behavior Analysis technique where we can observe how the visual impaired children respond to some of the games that are offered. Based on the analysis, it was identified that visual impaired children can accept games that rely on other five senses such as hearing, smell and touch. Children with visually impaired condition also tend to be able to play games that have simple instructions and are not too complicated. But even so, visual impaired children still need assistance in doing recreation.